2018
DOI: 10.1172/jci92981
|View full text |Cite
|
Sign up to set email alerts
|

The NOTCH1/CD44 axis drives pathogenesis in a T cell acute lymphoblastic leukemia model

Abstract: NOTCH1 is a prevalent signaling pathway in T cell acute lymphoblastic leukemia (T-ALL), but crucial NOTCH1 downstream signals and target genes contributing to T-ALL pathogenesis cannot be retrospectively analyzed in patients and thus remain ill defined. This information is clinically relevant, as initiating lesions that lead to cell transformation and leukemia-initiating cell (LIC) activity are promising therapeutic targets against the major hurdle of T-ALL relapse. Here, we describe the generation in vivo of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 62 publications
(91 reference statements)
5
53
0
Order By: Relevance
“…The low expression of CD44 was associated with NOTCH1 mutations and the presence of STIL-TAL1 . CD44 has previously been described as NOTCH1 transcription target ( 11 ), and may explain this association. However, in relation to the TAL1 transcription factor, there are still no studies to date that demonstrate this association with CD44.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The low expression of CD44 was associated with NOTCH1 mutations and the presence of STIL-TAL1 . CD44 has previously been described as NOTCH1 transcription target ( 11 ), and may explain this association. However, in relation to the TAL1 transcription factor, there are still no studies to date that demonstrate this association with CD44.…”
Section: Discussionmentioning
confidence: 81%
“…The authors also demonstrated that treatment with CD44 blocking antibodies increased the sensitivity of leukemic cells to chemotherapeutics. In addition, CD44 was identified as a direct transcriptional target of NOTCH1 in murine model of T-ALL, where NOTCH1 binding sites were found in the CD44 promoter ( 11 ). In the same model, the occupation of leukemic cells in bone marrow, spleen and thymus during disease progression was shown to be dependent on CD44, and the inhibition of CD44 by anti-CD44 antibodies led to the eradication of established T-ALL in vitro ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cells expressing high levels of IRF8 and MPO were clearly distinct from the main thymocyte population that expressed CD7 and therefore most likely represent non T-lineage cells (Plum et al, 1999) . We also identified cells with intermediate expression of IRF8 and MPO , corresponding to immature T cell precursors as identified by the strong and Notch-dependent expression of CD7 ) and CD44 (García-Peydró et al, 2018) .…”
Section: Single Cell Transcriptome Profiling Of Immature Human Thymocmentioning
confidence: 92%
“…However, its contribution to LIC activity in hematologic cancers, although suggested [ 272 ], has not been formally proven until very recently. By using a novel mouse model of human T-ALL pathogenesis [ 276 ], this work showed that CD44 is a direct transcriptional target of NOTCH1, which is upregulated in NOTCH1-induced preleukemic blasts, facilitating their engraftment into the bone marrow niche, and supporting the LIC potential of T-ALL [ 276 ]. These results indicate that CD44 upregulation is a key event of T-cell leukemogenesis, a finding that concurs with the fact that T-ALL patients commonly display an aberrant expression of CD44 in leukemic blasts [ 277 ].…”
Section: Potential New Targets For T-all Immunotherapymentioning
confidence: 99%
“…These results indicate that CD44 upregulation is a key event of T-cell leukemogenesis, a finding that concurs with the fact that T-ALL patients commonly display an aberrant expression of CD44 in leukemic blasts [ 277 ]. Although no link of CD44 expression with prognosis and overall survival of T-ALL patients has been established [ 277 ], CD44 contributes to T-ALL maintenance and progression, likely by regulating LIC potential [ 278 ], as proved by anti-CD44 mAb administration in a PDX T-ALL model [ 276 ]. CD44 expression is also upregulated in Notch1-induced T-ALL leukemic cells treated with chemotherapeutic drugs, such as doxorubicin and dexamethasone, and contributes to T-ALL chemoresistance by modulating intracellular drug efflux [ 279 ].…”
Section: Potential New Targets For T-all Immunotherapymentioning
confidence: 99%